Analisis Faktor-Faktor Yang Mempengaruhi Perusahaan Melakukan Auditor Switching Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia periode 2009-2012 - Mardiyana, Erna, Fauzan S.E, Ak, M.si (2016)
This research aimed to know the factors that influence companies in Indonesia to do such auditor switching. Variables that used in this research are audit opinion, management changes, public accountant firm's size, client size, financial distress, and auditor switching. The population is all companies listed in Indonesian stock exchange in the period 2009-2012. Based on method purposive sampling, research sample total is 120 companies. Hypothesis in this research are tested by logistics regression. The results of this research can be concluded that the management changes, public accountant firm's size and client size effect auditor switching . On the other hand, other variables in this research such as audit opinion, financial distress do not have effect on company decision to do auditor switching. Keyword : audit opinion, management changes , public accountant firm's size, client size, financial distress, and auditor switching